2014
DOI: 10.1163/15685403-00003284
|View full text |Cite
|
Sign up to set email alerts
|

Dormant eggs of a calanoid copepod from tropical brackish aquaculture ponds

Abstract: Many Asian aquaculture farms cultivate copepods as live-feed for aquaculture species, as copepod nutritional and behavioural qualities are usually higher than those of traditional live-feeds (i.e., Artemia and rotifers). The most convenient method to use Zooplankton in aquaculture as live feed involves dormant eggs. In this study, to establish whether the copepod species of the tropical Taiwanese ponds exhibit quiescence of their eggs, several sediment samples were collected from the ponds and incubated at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Most studies on copepod resting eggs are conducted by extracting sediment (from cores) sampled in the field and subsequently incubating it at different environmental conditions that trigger hatching of the sedimented eggs (e.g., Marcus, 1984;Engel and Hirche, 2004;Masero andVillate, 2004, Dahms et al, 2006;Sichlau et al, 2011;Beyrend-Dur et al, 2014). In field studies, age determination of eggs is often done by isotopic analysis of 210 Pb and/or 137 Cs for estimating the age of the sediment in which the eggs reside (Dahms et al, 2006;Jiang et al, 2006;Katajisto, 2006;Sichlau et al, 2011).…”
Section: Common Approaches To Study Age and Viability Of Copepod Restmentioning
confidence: 99%
“…Most studies on copepod resting eggs are conducted by extracting sediment (from cores) sampled in the field and subsequently incubating it at different environmental conditions that trigger hatching of the sedimented eggs (e.g., Marcus, 1984;Engel and Hirche, 2004;Masero andVillate, 2004, Dahms et al, 2006;Sichlau et al, 2011;Beyrend-Dur et al, 2014). In field studies, age determination of eggs is often done by isotopic analysis of 210 Pb and/or 137 Cs for estimating the age of the sediment in which the eggs reside (Dahms et al, 2006;Jiang et al, 2006;Katajisto, 2006;Sichlau et al, 2011).…”
Section: Common Approaches To Study Age and Viability Of Copepod Restmentioning
confidence: 99%
“…However, scarce contribution is paid on tropical copepod species. Beyrend‐Dur, Dur, Souissi and Hwang () were the first to report that the eggs (unidentified type) of the tropical calanoid copepod, Acartia bilobata , collected from sediments of a brackish aquaculture pond in southern Taiwan remain viable after cold storage. This species has great aquaculture potential because of their high productivity (Pan et al., ), and the feasibility of a quiescent cold‐induction protocol was preliminarily examined (Pan, Souissi, Hwang & Souissi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in a water column of a few meters depth, the tank sediments are likely to host vast amounts of copepod eggs of one or the other categories (Sørensen et al 2007). The accumulation of eggs in such a sediment egg bank has never been documented and quantified systematically before, but Beyrend-Dur et al (2014) and van der Meeren et al (2014) state that resting eggs can be found in aquaculture pond sediments at high concentrations and can hatch at refilling. If a substantial amount of eggs happens to be present in the tank sediment, these eggs could be stored and used as a source of newly hatched nauplii as live feed in the daily management of these facilities such as what is done with Artemia, and has been proposed earlier for copepods indoor productions: 'hatch and feed' .…”
Section: Introductionmentioning
confidence: 99%